Study of Manure on Growth and Yield of White Glutinous Rice (Oryza Sativa L. Glutinosa) - siti nurjanah; Dewi Ratna Nurhayati; Siswadi Siswadi (Innofarm:Jurnal Inovasi Pertanian, 2020)
Research on "Study of Manure on Growth and Yield of White Glutinous Rice (Oryza Sativa L. var. Glutinosa)" has been carried out from November 11th, 2019 to March 2th, 2020 in Donoudan Village, Ngemplak District, Boyolali Regency, the height of the place around 150 masl and the type of soil grumusol. This study uses a Complete Randomized Block Design (RAKL) with a single factor consisting of 10 kinds of treatments and repeated 3 times. Consisting D0, A1, A2, A3, K1, K2, K3, S1, A2, A3. Obsevation was carried out by taking 8 sample plants at each treatment. Data from this study were analyzed with the Uji Duncan’s Multiple Range Test (DMRT) at 5%, the parameters observed included plant height, number of tillers per family, leaf color, panicle length of number of productive tillers, weight of grain harvest per plot, weight of grain harvest per clump, and weight of 1000 grains. The results of the research, it was shown that the application of manure affected the length of panicle, the number of productive tillers, the weight of dried grains per clump, the weight of unhulled rice per plot and the weight of 1000 grains. The use of chicken manure with a dose of 4,5 kg/plot gave the highest yield of grain weight per plot which was 1820,90 grams (8,67 tons/ha), had a significant effect with control without manure (increase of 38,73) but not significant effect by providing treatmen of cow manure and goat manure.